Antifungal defensins and their role in plant defense - Lacerda, Ariane; Vasconcelos, Érico A.; PELEGRINI, PATRICIA B.; Grossi-de-Sa, Maria Fatima (Frontiers in Microbiology, 2014)
Since the beginning of the 90’s lots of cationic plant, cysteine-rich antimicrobial peptides (AMP) have been studied. However, Broekaert only coined the term “plant defensin” in 1995, after comparison of a new class of plant antifungal peptides with known insect defensins. From there, many plant defensins have been reported and studies on this class of peptides encompass its activity towards microorganisms and molecular features of the mechanism of action against bacteria and fungi. Plant defensins also have been tested as biotechnological tools to improve crop production through fungi resistance generation in organisms genetically modified (OGM). Its low effective concentration towards fungi, ranging from 0.1 to 10 µM and its safety to mammals and birds makes them a better choice, in place of chemicals, to control fungi infection on crop fields. Herein, is a review of the history of plant defensins since their discovery at the beginning of 90’s, following the advances on its structure conformation and mechanism of action towards microorganisms is reported. This review also points out some important topics, including: (i) the most studied plant defensins and their fungal targets; (ii) the molecular features of plant defensins and their relation with antifungal activity; (iii) the possibility of using plant defensin(s) genes to generate fungi resistant GM crops and biofungicides; and (iv) a brief discussion about the absence of products in the market containing plant antifungal defensins.